SPE Annual Technical Conference and Exhibition 2006
DOI: 10.2118/102637-ms
|View full text |Cite
|
Sign up to set email alerts
|

Navigating and Imaging in Complex Geology with Azimuthal Propagation Resistivity while Drilling

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractReservoir navigation with LWD resistivity has traditionally relied on matching real time measurements with ideal logs. Reservoir navigation engineers initially build one or more resistivity models including all expected resistivity boundaries such as oil-water contact, reservoir to cap rock interface, faults and unconformities. Then, during drilling, they direct the well and update the earth model by matching actual measurements with forward response model da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The axial transmitting and orthogonal receiving antenna is the basic antenna unit, which is used in instruments, such as AziTrak and VisiTrak (Bell et al, 2006;Rabinovich et al, 2011), as shown in Figure 1D. Using this antenna structure, the crosscoupled component signal V zx can be measured and the interface information can be directly reflected.…”
Section: Orthogonal Receiving Antennamentioning
confidence: 99%
See 1 more Smart Citation
“…The axial transmitting and orthogonal receiving antenna is the basic antenna unit, which is used in instruments, such as AziTrak and VisiTrak (Bell et al, 2006;Rabinovich et al, 2011), as shown in Figure 1D. Using this antenna structure, the crosscoupled component signal V zx can be measured and the interface information can be directly reflected.…”
Section: Orthogonal Receiving Antennamentioning
confidence: 99%
“…One type of electromagnetic boundary detection logging tool, Schlumberger's Periscope and Geosphere, uses a tilted antenna (Li et al, 2005;Omeragic et al, 2006;Antonsen et al, 2014;Seydoux et al, 2014;Zhu et al, 2021;Wu et al, 2022). The other type, by AziTrak and ViziTrak of Baker Hughes, uses an orthogonal antenna (Bell et al, 2006;Wang et al, 2007;Fang et al, 2008;Rabinovich et al, 2011). According to the detection range, EM boundary detection LWD tools can be divided into the azimuthal electromagnetic resistivity LWD tool (Hawkins et al, 2015) and the ultra-deep azimuthal electromagnetic resistivity LWD detection logging tool (Wu et al, 2019;Nemushchenko et al, 2022;Zhu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…A remote boundary introduces asymmetry in the Eddy currents and therefore a measurable signal in the receiver (e.g. Bell et al, 2006). Because of its geometry, this measurement is azimuthally sensitive.…”
Section: Downhole Extra-deep Em Systemmentioning
confidence: 99%
“…For example, a 10 ohmm reservoir with a 1 ohmm shale boundary or underlain by a 1ohmm water zone, have the same contrast in resistivity with a 1000 ohmm reservoir with a 100 ohmm shale boundary. The tool's principle of operation is described in detail in [Bell et al, 2006]. During the well planning stage, it was thus necessary to determine if azimuthal resistivity would be effective in achieving the well objective.…”
Section: Well Planningmentioning
confidence: 99%